Pengaruh Terapi Zikir terhadap Pasien Skizofrenia dengan Halusinasi Pendengaran di Rumah Sakit Jiwa Aceh - Sinta Asmaya; Syukriadi Syukriadi; Mansuriza Mansuriza (Lembaga Pengembangan Kinerja Dosen, 2025)
Schizophrenia is a severe mental disorder often accompanied by various psychopathological manifestations, one of which is auditory hallucinations that limit social functioning and reduce the quality of life of affected individuals. Dhikr therapy, as a psychoreligious approach, is believed to provide inner peace and reduce the intensity of hallucinatory symptoms. This study aims to evaluate the effectiveness of dhikr therapy among schizophrenia patients with auditory hallucinations who were treated at Aceh Mental Hospital. The research employed a quasi-experimental design with a pretest–posttest model and purposive sampling technique, involving 15 patients experiencing auditory hallucinations. The intervention was conducted for three consecutive days, with each session lasting 10–20 minutes and consisting of a sequence of dhikr recitations including istighfar, tasbih, tahmid, and takbir. The severity of hallucinations was measured using the Auditory Hallucination Rating Scale (AHRS). Data analysis was performed using the Wilcoxon test. The results showed a significant decrease in auditory hallucination scores with a p-value of 0.001. These findings indicate that dhikr therapy is effective in helping patients manage hallucinatory symptoms and may serve as a non-pharmacological therapeutic alternative in psychiatric nursing care for schizophrenia patients